Effect of physical exercise on brain and lipid metabolism in mouse models of multiple sclerosis. (October 2017) - Houdebine, Léo; Gallelli, Cristina Anna; Rastelli, Marialetizia; Sampathkumar, Nirmal Kumar; Grenier, Julien
Graphical abstract: Highlights: Physical exercise influences different pathophysiological aspects of MS:. Clinical outcomes. Oligodendrocytes and neurons defects. Oxidative stress and inflammation. Blood brain barrier integrity that could lead to attenuate the alteration of brain cholesterol homeostasis observed in MS. Abstract: Multiple sclerosis (MS) is a central nervous demyelinating disease characterized by cyclic loss and repair of myelin sheaths associated with chronic inflammation and neuronal loss. This degenerative pathology is accompanied by modified levels of oxysterols (oxidative derivatives of cholesterol, implicated in cholesterol metabolism), highlighted in the brain, blood and cerebrospinal fluid of MS patients. The pathological accumulation of such derivatives is thought to participate in the onset and progression of the disease through their implication in inflammation, oxidative stress, demyelination and neurodegeneration. In this context, physical exercise is envisaged as a complementary resource to ameliorate therapeutic strategies. Indeed, physical activity exerts beneficial effects on neuronal plasticity, decreases inflammation and oxidative stress and improves blood-brain integrity in extents that could be beneficial for brain health. The present review attempts to summarize the available data on the positive effect of physical exercise to highlight possible links between physical activity and modulation of cholesterol/oxysterol homeostasis in MS.